(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: This study aims to describe the prevalence and characteristics of depressive disorders among patients with colorectal cancer treated at the Oncology Center of Thai Binh General Hospital during 2024-2025. Subjects and methods: A cross-sectional study design was employed to investigate the current status of certain depressive disorders among patients with colorectal cancer undergoing treatment at the Oncology Center of Thai Binh General Hospital during the period 2024-2025. Results: Depressive disorders were present in 26% of patients with colorectal cancer. The prevalence of major depressive disorder was 13.7%. The most commonly observed condition was adjustment disorder with depressive reaction, accounting for 47.1%. Regarding core symptoms of depression, all patients exhibited depressed mood, and the majority experienced a loss of interest or pleasure and reduced energy, leading to increased fatigue and decreased activity levels. In terms of common depressive symptoms, all patients reported sleep disturbances. Conclusion: The onset of depression in patients with colorectal cancer was observed following the initial diagnosis or during periods of disease progression.